633. Bictegravir/Emtricitabine/Tenofovir Alafenamide (B/F/TAF) Efficacy in Participants with Pre-Existing Primary Integrase Inhibitor Resistance Through 48 Weeks of Phase 3 Clinical Trials. (31st December 2020) - D'Antoni, Michelle L; Andreatta, Kristen; Acosta, Rima K; Chang, Silvia; Martin, Ross; White, Kirsten L
Abstract: Background: Pre-existing drug resistance can affect the efficacy of antiretroviral therapy. Studies in treatment-naïve and virologically suppressed participants have demonstrated safety and efficacy of B/F/TAF, including in patients with M184V/I mutations. In this pooled analysis, we investigated virologic outcomes after 48 weeks of B/F/TAF treatment in individuals with pre-existing integrase strand transfer inhibitor resistance (INSTI-R). Methods: Although INSTI-R was prohibited per study entry criteria, pre-existing INSTI-R (T66A/I/K, E92G/Q, F121Y, Y143C/H/R, S147G, Q148H/K/R, N155H/S, R263K) was evaluated in participants from studies 1489, 1490, 1844, 1878, 4030. INSTI-R was assessed by historical genotypes and/or retrospective deepType HIV assay (Seq-IT, Germany), GenoSure IN, GenoSure Archive (Monogram Biosciences). Virologic outcomes were defined by last on-treatment observation carried forward (LOCF) method. Results: Pre-existing primary INSTI-R substitutions were detected in 20/1907 participants (1.0%) after enrolment. Of the 20, 75% were male, 30% white, and 85% had HIV-1 subtype B, baseline median CD4 counts of 594 (IQR 517, 700), and median age of 52 (43, 59) years. One participant was treatment-naïve with a baseline viral load of 30, 000 copies/ml and had Q148H (+ G140S on plasma RNA genotype) and was sensitive to bictegravir (< 2.5-fold change). The other 19 participants were virologically suppressed and had E92G (n=3), Y143C (n=2), Y143H (n=4), S147G (n=2), N155S (n=1), Q148H (n=3), Q148K (n=1), Q148R (n=1), or R263K (n=2) INSTI-R mutations by DNA genotype. The treatment-naïve individual was suppressed by Week 4 and maintained viral loads of < 50 copies/mL through Week 48. All suppressed participants had HIV RNA < 50 copies/mL throughout Week 48. All study participants had virologic success by LOCF (< 50 copies/mL) at Week 48. Conclusion: Participants with primary INSTI-R substitutions had or maintained virologic suppression through 48 weeks of B/F/TAF treatment. Consistent with the potent in vitro activity of bictegravir against many INSTI-R mutations, these virologic outcomes suggest that B/F/TAF may have potential as a treatment option for some patients with pre-existing INSTI-R, if confirmed by further studies. Disclosures: Michelle L. D'Antoni, PhD, Gilead Sciences (Employee, Shareholder) Kristen Andreatta, MSc, Gilead Sciences (Employee, Shareholder) Rima K. Acosta, BS, Gilead Sciences, Inc. (Employee, Shareholder) Silvia Chang, Masters, Gilead Sciences (Employee, Shareholder) Ross Martin, PhD, Gilead Sciences (Employee, Shareholder) Kirsten L. White, PhD, Gilead Sciences, Inc. (Employee, Shareholder)